STRATEGIES FOR ENSURING BUSINESS RESILIENCE UNDER UNCERTAINTY: TRENDS, RISKS, AND ADAPTIVE MODELS - Halushka, Zoia (SWorld-Ger Conference proceedings, 2025)
The paper examines contemporary strategies for ensuring business resilience under conditions of global uncertainty. It substantiates the transition from crisis response to systemic strategic adaptability that integrates technological innovation, flexible